Lack of Association between Seropositivity of Vasculopathy-Related Viruses and Moyamoya Disease - Nakamura, Yasuhisa; Mineharu, Yohei; Kamata, Takahiko; Funaki, Takeshi; Miyamoto, Susumu; Koizumi, Akio; Harada, Kouji H. (Journal of stroke and cerebrovascular diseases, 2022)
Although the association between genetic factors, such as RNF213 mutations, and moyamoya disease (MMD) has been well investigated, environmental factors are largely undetermined. Thus, we aimed to examine whether viral infection increases the risk of MMD. To eliminate the effect of presence or absence of the RNF213 p.R4810K mutation, the entire study population was positive for this mutation. We collected whole blood from 111 patients with MMD (45 familial and 66 sporadic cases) and 67 healthy volunteers, and we measured the immunoglobulin G titer of 11 viruses (cytomegalovirus, varicella-zoster virus, measles virus, rubella virus, herpes simplex virus, mumps virus, Epstein–Barr virus, human parvovirus B19, human herpesvirus 6 [HHV6], human herpesvirus 8, and John Cunningham virus) that were presumed to be associated with vasculopathy using the enzyme-linked immunosorbent assay. Positivity for past viral infection was determined by cut-off values obtained from previous reports and the manufacturer's instructions, and the positive rate was compared between cases and age- and sex-matched controls. We performed familial case-specific and sporadic case-specific analyses, as well as a case–control analysis. There was no significant difference in the positive rate between the case group and the control group in any of the analyses. A significant difference was only observed in the combined case–control analysis for HHV6 (p = 0.046), but the viral antibody-positive rate in control individuals was higher than in MMD cases. Our cross-sectional study suggest that the investigated 11 viruses including HHV6 are unlikely to have an impact on MMD development.